Effect of soil type and depth of sowing on the seedling emergence, growth and yield performance of chinese long bean - S.M. Rezaul Karim; Mohd Fazril Mohd Zayadi; Shafiqur Rahman (2014)
Planting depth and soil type are important growth conditions which affect the performance of